Thymic Versus Induced Regulatory T Cells – Who Regulates the Regulators? - Povoleri, Giovanni A.; Scotta, Cristiano; Nova-Lamperti, Estefania A.; John, Susan; Lombardi, Giovanna; Afzali, Behdad (Frontiers in Immunology, 2013)
Physiological health must balance immunological responsiveness against foreign pathogens with tolerance towards self-components and commensals. Disruption of this balance causes autoimmune diseases/chronic inflammation, in case of excessive immune responses, and persistent infection/immunodeficiency if regulatory components are overactive. This homeostasis occurs at two different levels: at a resting state to prevent autoimmune disease, as autoreactive effector T-cells (Teffs) are only partially deleted in the thymus, and during inflammation to prevent excessive tissue injury, contract the immune response and enable tissue repair. Adaptive immune cells with regulatory function (“regulatory T-cells”) are essential to control Teffs. Two sets of regulatory T cell are required to achieve the desired control: those emerging de novo from embryonic/neonatal thymus (“thymic” or tTregs), whose function is to control autoreactive Teffs to prevent autoimmune diseases, and those induced in the periphery (“peripheral” or pTregs) to acquire regulatory phenotype in response to pathogens/inflammation. The differentiation mechanisms of these cells determine their commitment to lineage and plasticity towards other phenotypes. tTregs, expressing high levels of IL-2 receptor alpha chain (CD25), and the transcription factor Foxp3, are the most important, since mutations or deletions in these genes cause fatal autoimmune diseases in both mice and men. In the periphery, instead, Foxp3+ pTregs can be induced from naïve precursors in response to environmental signals. Here, we discuss molecular signatures and induction processes, mechanisms and sites of action, lineage stability and differentiating characteristics of both Foxp3+ and Foxp3- populations of regulatory T cells, derived from the thymus or induced peripherally. We relate these predicates to programs of cell-based therapy for the treatment of autoimmune diseases and induction of tolerance to transplants.